SPATIAL DISTRIBUTION OF MICROPLASTIC ABUNDANCE IN PATEGURAN ESTUARY, PASURUAN, EAST JAVA, INDONESIA - Prastyo Hendro Dwi Cahyono; Hariyadi Hariyadi; Anis Zubaidah (IJOTA (Indonesian Journal of Tropical Aquatic), 2024)
Indonesia ranks 2 countries with a high level of plastic pollution. Plastic waste entering the Indonesian sea is estimated to reach 0.48-1.29 million metric tons/year. This microplastic is the result of the degradation of plastic waste and textile waste that decomposes to small size in a very long time . The river is the headwaters of various rivers and streams which have the potential to carry plastic particles . This makes it likely that the waters of the north sea are also polluted by microplastics, one of which is sourced from rivers . This research was conducted to find out how contaminated the northern sea waters by microplastics, especially estuary areas. The area sampled to be studied is one of the river estuaries in Pasuruan, at the Pasuruan river estuary which is then analyzed at the Laboratory of Fisheries, University of Muhammadiyah Malang . The results of the analysis found three types of microplastics, fiber, film, and fragments. Station 2 is the sampling area of the middle estuary area which results in the most abundance of microplastic abundance of 611111.1 particles/m3 . Microplastic types found were dominated by fiber types up to 55%. The most common microplastics found in the estuary waters of the Pateguran river are microplastics with sizes ranging from 1-333.3 µm . Based on FTIR results, it is suspected that there are microplastics derived from nylon or polyamide (PA) and polypropylene (PP) types.